A key role for allostatic overload in ASD and other disorders. Commentary on "An integrative model of autism spectrum disorder: ASD as a neurobiological disorder of experienced environmental deprivation, early life stress, and allostatic overload" by William M. Singletary, MD. Issue 1 (2nd January 2016) - McEwen, Bruce S.
Abstract : The brain is the central organ of perceiving, responding, and adapting to life experiences, and it communicates in a reciprocal manner with the rest of the body via autonomic, neuroendocrine, metabolic, and immune mediators that are essential for adaptation to stressful experiences by a process referred to as "allostasis." Singletary reminds us that the impaired ability of the ASD-prone infant to respond to the "serve and return" interaction with parents leads to a state of frustration and chronic stress resulting in the cumulative "wear and tear" of adapting to chronic stress, called "allostatic overload, " that worsens the trajectory of the disorder and helps shape brain architecture, behavior, and systemic physiology. Singletary says that successful treatment must recognize the deviation from a normal developmental course as early as possible and intervene to redirect it. He cites examples in children where this has made a huge difference. Thus, the epigenetic plasticity of the brain is key to the development of successful interventions and the continuing plasticity of the brain throughout the life course gives hope for further beneficial interventions.